Oral Insulin Delivery: Novel Strategies - Hirlekar, Dr. Rajashree S. (Asian Journal of Pharmaceutics (AJP), 2017)
Diabetes is a disorder related to the deficiency in the secretion or action of insulin - a peptide hormone synthesized by the Î² cells of islets of pancreas. Insulin is given by the subcutaneous (SC) route. Patient non-compliance is frequent with the SC route. To remove the hurdle related to oral insulin delivery various efforts have been made. Thus, oral insulin is a dream of patients. Nanotechnology is an emerging era of science which provides an innovative means to detect, diagnose and to treat a disorder. Nanocarriers have been garnering more attention recently because of their size in nano range and greater surface area. These characteristics improve their absorption in contrast to bigger carriers. This article gives an insight into different novel approaches to get better oral insulin delivery. These novel formulations improve bioavailability; absorption problems associated with insulin and give protection from enzymatic degradation. More research has been done on nanoparticles (NPs) as a carrier to deliver insulin orally. At present, researchers from both industries as well as academics are working on oral insulin. With this struggle, the dream of researcher to deliver insulin orally will turn out to be a reality in the future.